Athletic trainer accessibility in U.S. high schools: A systematic review and meta-analysis - Mologne, M. S.; Troyer, S. C.; Haider, A. A.; Hardi, A.; Evans, C.; Kuhn, A. W. (Current Sports Medicine Reports, 2025)
We sought to calculate the pooled access to athletic trainers at secondary and high schools within the United States, and to evaluate barriers to athletic trainer staffing among these schools. Data on full-time access and any access to an athletic trainer as well as factors that contributed to accessibility were collected. Twenty-four studies were included in the final review. Two-thirds (66.4%) of the schools in the included studies had any access to an athletic trainer, while only one-third (34.6%) of schools had full-time access. Five common themes arose that diminished a school's ability to access an athletic trainer — smaller school size and lower student athlete numbers, rural school location, private school status, and low socioeconomic status of the region. Efforts to increase funding and access to athletic trainers for high school athletes may help provide numerous economic and health-related benefits both in the short and long term.